2016
DOI: 10.1097/aln.0000000000001068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Foundation for Anesthesia Education and Research Medical Student Anesthesia Research Fellowship Program Participants’ Scholarly Activity and Career Choices

Abstract: Background The Foundation for Anesthesia Education and Research Medical Student Anesthesia Research Fellowship (MSARF) program is an 8-week program that pairs medical students with anesthesiologists performing anesthesia-related research. This study evaluated the proportion of students who published an article from their work, as well as the percentage of students who entered anesthesiology residency programs. Methods A list … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Undoubtedly, such fellowships should affect research productivity especially that participants are fully dedicated and are not overwhelmed by any clinical demand. One study evaluated an anaesthesia research fellowship programme and revealed that 42% of the projects were published, and that 58% of the students were able to access an anaesthesiology residency programme [13].…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, such fellowships should affect research productivity especially that participants are fully dedicated and are not overwhelmed by any clinical demand. One study evaluated an anaesthesia research fellowship programme and revealed that 42% of the projects were published, and that 58% of the students were able to access an anaesthesiology residency programme [13].…”
Section: Discussionmentioning
confidence: 99%
“…international study on summer research program amongst undergraduate reported 30% research articles being coauthored by medical students. 28 In another study, authors reviewed 25152 publications in the Medline-indexed journals affiliated to world"s top 10 universities and found out that 2537 (10.1%) articles contained atleast one undergraduate medical student as co-author. 29 A study (n=346) in a Sri Lanka medical university found that 57.6% students had shared their research finding in some scientific conference whereas only 1.73% had published in indexed journal as author.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes from these programs include 16% of medical fellows and 20% of Cloister graduates engaging in academic careers and 24% of medical fellows and 21% of Cloister receiving NIH awards [ 10 ]. Though these results may be discouraging, there is evidence to suggest that exposure to research experiences may increase the number of physician-scientists [ 11 14 ] and is associated with improved productivity and more informed trainees and has shown to result in an increased interest toward research [ 16 ]. A recent meta-analysis suggests medical students whom participate in research are over three times as likely to report interest in research engagement in their future careers, are six times as like to purse ‘academic careers’ as compared to their “untreated” peers and are twice as likely to academically outperform their peers [ 15 ].…”
Section: Introductionmentioning
confidence: 99%